Paths out of poverty: An eclectic and idiosyncratic review of analytical approaches - Díaz-Bonilla, Eugenio; Constenla-Villoslada, Susana (Chinese Academy of Agricultural Sciences, 2021)
This paper briefly reviews different debates about approaches for paths out of poverty, considering several views, from the analysis of specific policies to more general or systemic considerations. The contribution of this paper is to present a broad outline of those debates and to serve as an illustration of the complexity of analyzing paths out of poverty. It discusses in sequence, the more microeconomic approach of evaluation of individual policies for poverty alleviation; then it moves broader issues of growth and development strategies, and macroeconomic policies, and their links to the persistence or reduction of poverty; and finally discusses the topic of institutions, related to how decisions are made and enforced in societies at the previous three levels. There is a section with conclusions.